Signal Interference in WiFi and ZigBee Networks - Shi, Gaotao; Li, Keqiu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book systematically summarizes the fundamentals of WiFi and ZigBee from different levels and provides the detailed theoretical and experimental results for signal interference between these two wireless data transmission technologies. The existing mechanisms and methods of interference mitigation, avoidance and co-existence are carefully explored. Both collaboration and cross-technology communication between WiFi and ZigBee are also introduced as key research trends. Due to the popularity of WiFi and ZigBee, which share the same ISM frequency band, interference is a common problem and addressed in a wide range of literature. This book condenses the newest research results into an approachable format. This is an essential resource for professionals and students in wireless networks as well as network engineers, designers, or planners seeking a backbone of knowledge in WiFi and ZigBee networks. .
Keywords: Computer Engineering; Computer communication systems; Application software; Information Systems Applications (incl. Internet).